Thrombotic micro-angiopathy due to Strongyloides stercoralis hyperinfection - Manon C. Stam-Slob; Sef J.L.W. van den Beuken; René van der Griend; Lenneke E.M. Haas; Jeroen P.H.M. van den Wijngaard; Serena Slavenburg; Sanjay U.C. Sankatsing (Clinical Infection in Practice, 2022)
Background: A parasitic Strongyloides stercoralis infection is a common disease in endemic (sub)tropical areas. It may persist for years due to auto-infection. Most patients have no or mild respiratory, cutaneous, and gastrointestinal symptoms. Case Report: A 61-year-old female was hospitalized at the Intensive Care Unit with acute respiratory distress requiring mechanical ventilation and eosinophilia. Feces Baermann test and bronchoalveolar lavage showed S. stercoralis larvae, confirming the diagnosis of S. stercoralis hyperinfection syndrome. Remarkably, she suffered from Coombs negative hemolysis, thrombocytopenia and acute renal insufficiency. Following thorough examinations, we arrived at the diagnosis thrombotic micro-angiopathy caused by S. stercoralis hyperinfection syndrome. Full recovery was achieved following two weeks of oral treatment with ivermectin. Results: Severe S. stercoralis hyperinfection syndrome can trigger thrombotic micro-angiopathy and is easily treated with ivermectin. Conclusion: A small proportion of S. stercoralis infections may develop into severe systemic disease with high mortality and morbidity rate, including thrombotic micro-angiopathy.